Ultrasound-assisted crystallisation of magnesium hydroxide from seawater - Jakić, Jelena, kemijska tehnologinja (Array, 2020)
High purity magnesium hydroxide has been synthesised from seawater with the addition of dolomite lime as reagent. High intensity ultrasound-assisted crystallization of magnesium hydroxide was carried out during precipitation with the intention to obtain fine particles of Mg(OH)2 as well as to prevent their agglomeration. Investigations were conducted on magnesium hydroxide samples in the form of sludge and voluminous powder. The composition, morphology, and properties of the product were determined by chemical, XRD, FTIR, and SEM/EDS analysis. The particle size distribution was detected by the laser light scattering method. The results showed that the mean particle size of magnesium hydroxide sludge was 5.75 µm, while voluminous powder was 7.58 µm. The morphology of magnesium hydroxide voluminous powder was in the form of aggregated filamentous (up to 300 nm in size) or flake structures.